Migration outflow and remittance patterns in Indonesia national as well as subnational perspectives - Bachtiar, Palmira Permata (Philippine Journal of Development, 2011)
The article compares and contrasts the scale and composition of workers` outflow and remittance flow from 1994 to 2012 at the national level and in East Java and West Nusa Tenggara--two big migrant-sending provinces. Analysis over the longer period gives a better understanding of contemporary characteristics of volatility in labor deployment. We argue that level of deployment is not only explained by substantive factors--such as economic shocks, government policy, and epidemic--but also by technical factors, such as the recording system. If flawed records are not immediately corrected, policymakers will not be well informed in establishing correct policy relevance.